Maturitas, Indikator Keuangan dan Kesehatan Keuangan: Bukti Dari Indonesia - Utami, Martiana Riawati; Sumadi, Bella Madiana (Manajemen & Bisnis Jurnal, 2025)
This study aims to investigate the effect of firm's life cycle and financial indicators on financial health. The number of publicly traded companies declared delisted on the Indonesia Stock Exchange indicates that the firm's financial health is unstable. To investigate, the researchers conducted an analysis of panel data using financial ratios from life cycle, liquidity, leverage, and profitability in manufacturing companies listed on Indonesia Stock Exchange for period 2017 to 2019. The final sample obtained in this study consisted of 109 companies with a total 316 observations. Researchers found that firm's life cycle has a positive effect on financial health because the maturity cycle causes the firm to be more stable in running its business activities. Then, liquidity has no effect on financial health due to differences in the firm's ability can not be generalized. Furthermore, leverage has a negative effect on financial health because it is based on the firm's decision to use internal funding to minimize financial risk. Finally, profitability has a positive effect on financial health because it reflects the firm's operational performance. Therefore, it is necessary to understand the factors that have the opportunity to determine the firm's financial health